1987
DOI: 10.1104/pp.83.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Agrobacterium tumefaciens Strain A281 on Legumes

Abstract: This study addresses the basis of host range on legumes of Agrobacterium tumefaciens strain A281, an LL-succinamopine strain. We tested virulence of T-DNA and vir region constructs from this tumor-inducing (Ti) plasmid with complementary Ti plasmid re,gions from heterologous nopaline and octopine strains.Agrobacterium tumefaciens is the etiologic agent of crown gall. Oncogenic strains ofA. tumefaciens harbor large plasmids, called Ti2 plasmids (for review, see Ref. 17). Part of the Ti plasmidthe T-DNA-is trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…The resistance is not specific to strain B6: with three diverse wide host range strains, tumors on Sweet Snap were consistently much smaller than on other genotypes. Strain A281 has been reported to be hypervirulent on several species, including pea (8)(9)(10), as a result of enhanced activity of vir genes due to increased expression of the transcriptional activator virG (10). Sweet Snap as well as other genotypes responded to increased vir gene activity in A28 1, but tumors induced on other genotypes were more than 100% larger than those that developed on Sweet Snap.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance is not specific to strain B6: with three diverse wide host range strains, tumors on Sweet Snap were consistently much smaller than on other genotypes. Strain A281 has been reported to be hypervirulent on several species, including pea (8)(9)(10), as a result of enhanced activity of vir genes due to increased expression of the transcriptional activator virG (10). Sweet Snap as well as other genotypes responded to increased vir gene activity in A28 1, but tumors induced on other genotypes were more than 100% larger than those that developed on Sweet Snap.…”
Section: Discussionmentioning
confidence: 99%
“…Belanger et al (23) showed that individual virA genes may be particularly suited to function in certain genetic backgrounds, and Krishnamohan et al (183) recently demonstrated that Ti plasmids may have evolved to optimize specific combinations of virA, virG, and vir boxes. As noted above, the Ti-plasmid pTiBo542 in the C58 chromosomal background is hypervirulent on certain legume species, possibly because of the associated virG gene (41, 146, 159), but not in its native Bo542 chromosomal background (143). Recent results from my laboratory indicate that vir gene induction and T-strand production by and transformation efficiency of particular Agrobacterium strains may not correlate well.…”
Section: Virulence Gene Expression and Plant Transformationmentioning
confidence: 96%
“…For example, the Ti plasmid pTiBo542, when in its natural host strain A. tumefaciens Bo542, directs limited tumorigenic potential when assayed on many leguminous plant species. However, when placed in the C58 chromosomal background, pTiBo542 directs strong virulence toward soybeans and other legumes (143). Finally, susceptibility to crown gall disease has a genetic basis in cucurbits (292), peas (272), soybeans (15,214,246), and grapevines (312) and even among various ecotypes of Arabidopsis thaliana (231).…”
Section: Agrobacterium "Species" and Host Rangementioning
confidence: 99%
“…Even within a species, different cultivars or ecotypes may show vastly different degrees of susceptibility to tumorigenesis by particular Agrobacterium strains [54][55][56]. These differences IBA 2 weeks after culture initiation.…”
Section: In Vitro Susceptibility Of Genotypes To Agrobacterium Tumefamentioning
confidence: 99%